2009
DOI: 10.1007/s11661-009-9988-9
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Delamination of Chromium Thin Films on Polymer Substrates

Abstract: New emerging technologies in the field of flexible electronic devices require that metal films adhere well and flex with polymer substrates. Common thin film materials used for these applications include copper (Cu) with an adhesion interlayer of chromium (Cr). Copper can be quite ductile and easily move with the polymer substrate. However, Cr is more brittle and fractures at lower strains than Cu. This study aims to examine the fracture and subsequent buckling and delamination of strained Cr films on polyimid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…However, numerous studies have shown that thin film coatings on ductile substrates will fracture at low strains. Examples of thin films with low fracture strain of less than 1% include SiO 2 on various polymer substrates [1,2], Chromium (Cr) on polyimide [3], Ta on polyimide [4], and diamond-like carbon (DLC) on stainless steel [5], with the exact fracture values dependent on film thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies have shown that thin film coatings on ductile substrates will fracture at low strains. Examples of thin films with low fracture strain of less than 1% include SiO 2 on various polymer substrates [1,2], Chromium (Cr) on polyimide [3], Ta on polyimide [4], and diamond-like carbon (DLC) on stainless steel [5], with the exact fracture values dependent on film thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…These undergo multiple failure mechanisms such as delamination [4], channel cracking [5,6] and surface cracking which can be coupled with time-dependent damage from load cycling [7] and environmental degradation [8]. While multiple techniques and analyses exist for studying delamination or channel cracking of deposited thin films, direct measurements of fracture toughness values are relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…[6]). Experimentally, a large volume of work has been carried out on the failure behaviour of coating layers of a wide range of properties on a variety of substrates, mainly metallic [7][8][9] and polymeric [10][11][12][13][14][15][16]. The failure of these coatings has been observed by optical microscopy, electron microscopy [17,18] and electrical resistance measurements [19][20][21], and the mechanics of crack initiation and propagation in a coating/substrate system are well understood [5,22].…”
Section: Introductionmentioning
confidence: 99%